Analisis Tematik Kata Ar-Riih dan Fenomena Angin di Indonesia - Dwi Yuliyanti; Yeti Dahliana; Abdullah Mahmud (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
The Qur'an discusses various types of good winds, including typhoons, storms, cold winds that destroy crops, strong winds that blow objects away, and winds that destroy unbelievers. Through a collection of subjects related to the winds of the Koran, a thematic strategy is used. The author of this research used qualitative methodology and a mawdu'iy (thematic) approach. Maudui's study method is a method of discussing verses according to certain topics or titles. The ideas presented are the aim of this research. Therefore, qualitative techniques are used which use various primary and secondary literature sources. The author then analyzes and correlates the phenomena that exist in Indonesia. Research shows that the west and east monsoon winds cross Indonesia's territory which is sandwiched between two continents and two oceans. These two winds have a big influence on seasonal conditions in Indonesia. Indonesia as a large country faces various types of natural and non-natural disasters. The type of wind that occurs most often in Indonesia is typhoons, strong winds, or typhoons that are so strong that they can damage everything around them. These two winds are the same as the explanation in Surah Al-Isra' verse 69 and Surah Yunus verse 22. Thus, the wind phenomena that occur in Indonesia are correlated and in accordance with the explanation of the verses of the Qur'an regarding various types of wind.